The decision of the International Olympic Committee on the participation of Russian athletes in the Olympic games - Rodríguez García, José (EUNOMÍA. Revista en Cultura de la Legalidad, 2016)
This paper analyzes the decision of the International Olympic Committee to prohibit the participation of Russian athletes for events related to doping, and decisions of the Court of Arbitration for Sport adopted after that decision. doi: http://dx.doi.org/10.20318/eunomia.2016.3282